The association between personal factors and hand musculoskeletal discomfort among computer office workers - Widia, Mirta; Lim, Shu Chin; Ezrin Hani, Sukadarin; Nazlin Hanie, Abdullah; Zayyinul Hayati, Zen (The Korean Institute of Industrial Engineers, 2024)
Hand musculoskeletal discomfort is common among computer office workers due to computer-related work. This study aims to determine the association between personal factors and hand musculoskeletal discomfort among computer office workers. A cross-sectional study was conducted among 143 computer office workers. The personal factors and prevalence of hand musculoskeletal discomfort were identified by using a socio-demographics questionnaire and the Cornell Hand Discomfort Questionnaire (CHDQ). The highest prevalence of hand musculoskeletal discomfort was found at the right wrist (41.06%). There is a significant difference between age, BMI, computer usage per week, and period of employment on hand musculoskeletal discomfort (p<0.05). The result also found that hand musculoskeletal discomfort was associated with age, BMI, computer usage per week, and employment period. Age was most significantly associated with hand musculoskeletal discomfort (p<0.05). This study highlighted a significant association between personal factors and hand musculoskeletal discomfort. The association between personal factors and hand musculoskeletal discomfort could be a preliminary guideline on computer tasks preventing work-related musculoskeletal disorders.